Late-Stage Presentation of Testicular Cancer Patients Attended a Specialized Hospital: Findings of a Crosssectional Study (Journal of Preventive and Social Medicine, 2022)
Background: Testicular Cancer (TC) is of interest and importance because its incidence has been increasing in most countries over the past four decades. The purpose of this study is to determine the frequency of patients with common histopathology, most common stage during presentation, biochemical and radiological findings, common levels of tumour markers.Methods: This cross-sectional study was carried out in the Department of Medical Oncology of National Institute of Cancer Research and Hospital (NICRH), Mohakhali, Dhaka, Bangladesh from July 2015 to June 2016. A total number of 52 patients were taken as study participants who are admitted as newly diagnosed at the NICRH. Data collection: tumour markers, USG of whole abdomen and chest X-ray were performed to all the patients for determination of the staging of the tumour.Results: The present study found the majority of the patients were found in stage III disease. Patients with Cryptorchidism needed to be educated regarding its early management to reduce the incidence of testicular tumour among them. It was observed that young people could be adequately knowledgeable and optimal awareness could be developed regarding early symptoms of the disease, then they may be found in earlier stage of their disease, which is curable with modern management method. Targeting to alter the cancer patients’ presentation by rising consciousness about TC, prognosis can be largely improved in future.Conclusion: This study was conducted to find out the features which were unknown in perspective of Bangladesh, so that burden of TC can be reduced, and prognosis can be further improved of this potentially curable disease.JOPSOM 2021; 40(1): 26-33